COUNTRY–CITY AND RURAL–URBAN RELATIONS IN THE TWENTIETH-FIRST CENTURY - Marafon, Glaucio José; Fortes, Gabriel Bias; Seabra, Rogério (Geo UERJ, 2021)
Introduction: The thought regarding the countryside/city relationship in modern times implies going beyond the past representations concerning the rural space, that is, overcoming the dichotomic proposal, conceived within a context of reaffirmation of the urban logic, and thus recognizing the city and the city/countryside couplet as elements bonded by the same, though diverse, logic, typical of the space production under the rule of capitalism. Objective: The work aims at systemizing a reflection on the countryside/city and rural/urban couplets, based on the understanding that the countryside and the city may be associated to the same flow of spatial production insofar as the terms rural and urban are articulated with each other, involving subjective aspects as identity, form and rhythm of life, relation with nature and social interactions among the agents that reproduce (or even reinvent) such subjectivities. Results: In spite of the dissociation between the rural/urban and countryside/city binomials, the academic debate can still find traces of the previous paradigm from the observation of territories whose rural/rural and city/urban association coincide. Conclusion: As the countryside and the city are consolidated as material structures based on the patterns of land-use and occupation, the rural and the urban transit to the immaterial sphere becoming constructions and social practices - both dynamic and changeable - that can occur both in the countryside and the city alike. This enables the existence of localities presenting aspects related both to the rural and the urban contexts, such as urbanized fields and rural cities, bearing in mind that these aspects (urbanities and ruralities) do not concern the technological level itself, but the constructions and social practices that sustain the urban or rural characters (or both).